Influence of jet milling and particle size on the composition, physicochemical and mechanical properties of barley and rye flours. (15th January 2017) - Drakos, Antonios; Kyriakakis, Georgios; Evageliou, Vasiliki; Protonotariou, Styliani; Mandala, Ioanna; Ritzoulis, Christos
Highlights: Finer barley and rye flours were produced by jet milling at two feed rates. Jet milling as well as its feed rate were of great importance. Particle size affected the composition and mechanical properties of flours. The solvent retention capacity profile was also affected by particle size. The effect of particle size depended on the botanical origin of the flour. Abstract: Finer barley and rye flours were produced by jet milling at two feed rates. The effect of reduced particle size on composition and several physicochemical and mechanical properties of all flours were evaluated. Moisture content decreased as the size of the granules decreased. Differences on ash and protein contents were observed. Jet milling increased the amount of damaged starch in both rye and barley flours. True density increased with decreased particle size whereas porosity and bulk density increased. The solvent retention capacity profile was also affected by jet milling. Barley was richer in phenolics and had greater antioxidant activity than rye. Regarding colour, both rye and barley flours when subjected to jet milling became brighter, whereas their yellowness was not altered significantly. The minimum gelation concentration for all flours was 16% w/v. Barley flour gels were stronger, firmer and more elastic than the rye ones.